VD_FINDINFO HC / 2010 / 34 vom 21. Oktober 2009 - VD Tribunal cantonal (2009)
TENTATIVEDROIT PÉNAL, LÉSION CORPORELLE SIMPLE, LÉGITIME DÉFENSE | 123 ch. 1 CP, 129 CP, 15 CP, 411 let. h CPP, 411 let. i CPP, 415 CPP